North Korea in the Eye of CNN Online News - Suhariant, Permata Azzizah Yuva Putri; Sukarno, Sukarno; Setiarini, Riskia; Wahyuningsih, Indah (PAROLE: Journal of Linguistics and Education, 2024)
It is inevitable that there are partialities to certain parties, one of which is news related to North Korea. CNN tends to release news by emphasizing negative aspects of North Korea, such as its nuclear program, human rights violations, and restrictive government policies. This study aims to prove the power of CNN as a media in constructing the image of North Korea. This research is qualitative research because the data used is not numerical data. This research uses the three-dimensional theory of Critical Discourse Analysis (CDA) by Norman Fairclough. The theory of Systemic Functional Linguistics (SFL) by M.A.K. Halliday is also used as a supporting theory to analyze the first dimension of CDA. The results showed that there is a partiality of CNN to the United States in writing news. Starting from the use of verbs that indicate the occurrence of violence, the existence of negative words, and the conflict factors that occur between the United States and North Korea are supporting aspects of the formation of a negative image of North Korea in public.